Ethnobiology! Until when will the colonialist legacy be reinforced? - Sofia Zank; Cristiane Gomes Julião; Adriana de Souza de Lima; Marciano Toledo da Silva; Carolina Levis; Natalia Hanazaki; Nivaldo Peroni (Journal of Ethnobiology and Ethnomedicine)
Abstract In this essay, we will present arguments for a negative answer to the debate question: “Is publishing ethnobiology data respectful of Indigenous and Local Knowledge holders’ rights?” We recognize that ethnobiological research has advanced in recognizing the rights of Indigenous Peoples and Local Communities (IPLC), but we believe that we still have a long way to go in deconstructing colonialism in ethnobiology. In order to be truly respectful, ethnobiologists need to collaborate with IPLC to achieve an ethical science with equity between knowledge systems, fostering the co-production of knowledge from an intercultural science perspective. This essay was written by a group of Brazilian scientists, both IPLC and non-IPLC, and reflects a perspective of the academic universe seen from the place we are, in this multicultural and imbalanced world.